Optimalisasi Pemasaran Maggot Melalui Platform E-Commerce: Pendampingan Kelompok Tani Ternak Tui Jati - Irmanuddin; Ely Ermawati; Ni Made Ayu Yowana; Samsul Mahrip; Sase Nogyran Andry Lia; Maslami, Vebera; Dwi Kusuma Purnamasari; Endang Purnama Dewi (Universitas Mataram, 2025)
This community service program was implemented to address the limited use of digital marketing tools and e-commerce platforms in promoting maggot-based products produced by the Tui Jati Livestock Farmer Group. Prior to the program, product marketing was conducted conventionally and remained confined to local buyers due to the absence of digital promotional media. The activities were carried out through several stages including initial assessment, formulation of instructional materials, delivery of thematic training sessions, and direct mentoring for establishing an online marketplace account. During the training, participants were guided to develop a complete business profile, prepare standard product images, write informative descriptions, set appropriate prices, and manage incoming inquiries from potential buyers. The outcomes demonstrate significant improvement in participants’ digital competencies, especially in organizing online storefronts, ensuring product visibility, and maintaining communication channels with consumers. In addition, participants were able to update their product listings independently and sustain account activity after the program. Overall, this community service initiative has successfully increased digital literacy, strengthened product commercialization, expanded market access opportunities, and positioned e-commerce as a practical and sustainable marketing approach for maggot-based products.